LIFE SATISFACTION, COPING STRESS STRATEGIES & MEDIA CONSUMPTION DURING COVID-19 PANDEMIC IN INDONESIA - Saputro, Iswan; Sari, Ratna Permata; Roudhotina, Wardah (Universitas Mercu Buana Yogyakarta, 2021)
The COVID-19 pandemic as a global health crisis may lead to psychological distress to some people. This study aims to identify the correlation between coping stress strategies and life satisfaction during the COVID-19 pandemic among Indonesians. Furthermore, this study also has the objective to identify the way people consume media during this pandemic. From 24 April to 6 May 2020, the researchers conducted an online survey using snowball sampling techniques towards 200 Indonesian people. The measurements of this study used Brief COPE, Satisfaction with Life Scale, and a survey to measure media consumption. The results showed that the respondents had a level of life satisfaction in the slightly satisfied category during the COVID-19 pandemic. Life satisfaction was positively correlated with emotion-focused (positive reframing, religion) and negatively correlated with dysfunctional coping (denial, behavioral disengagement, self-blame). On the other hand, the result of the survey showed that 79% of respondents reported have an increase in social media consumption since the pandemic. There was no significant difference in life satisfaction between respondents who experienced an increase in media consumption and those who did not. The most current media activities were looking for entertainment (77,5%), communicating to others (74,5%), and searching for COVID-19 updates (64,5%). These findings can be used to formulate psychological interventions during the COVID-19 pandemic and as a reference in making public health promotion through media following the characteristics of respondents' lifestyle and sociodemographic.